Nouvelle donne législative et causes de la criminalité « corporative » - Snider, Laureen (Criminologie, 1997)
This paper examines the ideological and political collapse of laws regulating corporate crime in North America. In an era where social control and criminalization are steadily increasing, corporate crime has been normalized, shorn of its negative, criminal implications, de-regulated in law. The paper asks why this has happened, looking first at the century-long battle waged by labour and other counter-hegemonic groups to censure and control the antisocial acts of corporations through the passage of criminal legislation. Second, it examines the role criminology as a discipline played in this process, and the subsequent replacement of criminological discourse and influence by the newly-ascendent law and economics movement, which has provided the much of the academic support for de-regulation. Both developments, it is argued, are linked to changes in global capitalism and the weakened nation-state. Finally, the paper argues that the removal of regulation through criminal or administrative law, and of its accompanying rhetorics of denunciation, has grave consequences for social policy. The structural and ideological forces of global capitalism that have normalized corporate crime have also provided ideal conditions for increases in its incidence and impact.